2005
DOI: 10.1073/pnas.0502575102
|View full text |Cite
|
Sign up to set email alerts
|

Emergent patterns of growth controlled by multicellular form and mechanics

Abstract: Spatial patterns of cellular growth generate mechanical stresses that help to push, fold, expand, and deform tissues into their specific forms. Genetic factors are thought to specify patterns of growth and other behaviors to drive morphogenesis. Here, we show that tissue form itself can feed back to regulate patterns of proliferation. Using microfabrication to control the organization of sheets of cells, we demonstrated the emergence of stable patterns of proliferative foci. Regions of concentrated growth corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
674
4
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 764 publications
(727 citation statements)
references
References 48 publications
31
674
4
1
Order By: Relevance
“…A number of biological studies have suggested that the long axes of cells (Jacobson and Gordon 1976) are key determinants of mitosis orientation (O'Connell and Wang 2000). Other relevant factors may include cell signalling, biochemical factors, mechanical stresses and tissue deformation (Brodland and Veldhuis 2002;Gong et al 2004;Nelson et al 2005). In turn, regularly oriented mitosis, regardless of its origin, has been implicated as a significant driver of tissue motions (Philip et al 1992;Brodland and Veldhuis 2002;Gong et al 2004).…”
Section: Results and Conclusionmentioning
confidence: 99%
“…A number of biological studies have suggested that the long axes of cells (Jacobson and Gordon 1976) are key determinants of mitosis orientation (O'Connell and Wang 2000). Other relevant factors may include cell signalling, biochemical factors, mechanical stresses and tissue deformation (Brodland and Veldhuis 2002;Gong et al 2004;Nelson et al 2005). In turn, regularly oriented mitosis, regardless of its origin, has been implicated as a significant driver of tissue motions (Philip et al 1992;Brodland and Veldhuis 2002;Gong et al 2004).…”
Section: Results and Conclusionmentioning
confidence: 99%
“…Adherent cells seem capable of both responding to applied mechanical forces (Tzima et al, 2005) and applying contractile forces to probe mechanical properties of the environment (Discher et al, 2005). The downstream responses include changes in migration (Pelham and Wang, 1997;Sheetz et al, 1998;Lo et al, 2000), cell-cell interactions (Guo et al, 2006), proliferation Nelson et al, 2005), differentiation (Engler et al, 2004(Engler et al, , 2006, and apoptosis . For cultured adherent cells, focal adhesions are thought to mediate mechanosensing through integrin-mediated anchorage to the extracellular matrix (Larsen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…c) Reproduced with permission. [72] Copyright 2005, National Academy of Sciences. d) Reproduced with permission.…”
Section: Geometrymentioning
confidence: 99%
“…Multicellular geometry can also feedback to regulate patterns of cell growth, with regions of high traction stress favouring growth and branching morphogenesis (Figure 5c). [72,73] Cells on a surface can sense and react to radii of curvature much larger than a single cell and regions with high local concave (convex) curvature favour (inhibit) tissue growth (Figure 5d). [74,75] On the other end of the size scale, surface nano-and microtopography influence size and shape of cell-matrix adhesion points and thus also play an important role in cell mechanotransduction, as well as in stem cell self-renewal and multipotency.…”
Section: Geometrymentioning
confidence: 99%